MANIPULASl POLA SADAP UNTUK MENINGKATKAN BASIL GETAH POHON AGATIS (AGATHIS SP.) - Ishak Sumantri; Dulsalam Dulsalam (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
Thia ptJPB preaenta the re1ult1 •of invatifOtion on tapping design1 manipulation to increae relin• yield of A,aihiaap. cawied out in Wono10bo Sub Fore1t Diatrict, Purworejo Fore1t District, Unit 11 Perum Perhutani Central Java, in 1989. The objective iB to (ind out the tapping design that can increaae retin yield. For thit purpo•, the 1lanted and horizontal tappi1111 daigna were applied. Data obtained were analysed by uaing neated desilnl with 2 x 6 'x 4 (acto1'1. The retult•are as foUowa : I. An awrage reain yie1d of .Agathia ap. in Wonoaobo Sub Foreat District was 2.4 7 gram/tree/day with the ro111e between O. 71 and 8.29 gram/tree/day.2. The Average rain y1Bld1 of Alatbia 1p. uting 1lanted and horizontal tapping design1 were 2.80 and 2.66 gram/tree/day, re1Pectively.3. The average rain yield• of Agathia 1p. in February, .March, April, .May and June were 1.88, 2.62, 2.62, 2.66 and 2.69 1n1m/tree/day, rapectively. .4. The average rain yields of Agathia 1p. at the fir•t, second, third and fourth tappings were. 2.36, 2.46, 2.63 and 2.66 gram/tree/day, respectively.5. The rain yields among tapping months were different significantly while the resin yields either between tappfn6 deligna or amorw tapping (requencie1 were not Bignificantly different. Compered to relin yield of horizontal tappin6 de.Wn. the rain yield of 1lanted ta ping deBign wa• 16% higher.